Business Model Canvas : Handy Food Dehydrator / Iqbal Ali Mohd Azman - Mohd Azman, Iqbal Ali (2020)
The first value from the product that obviously shown is the compactness of the product itself. The compactness of the product helps the owner to handle it easily and can store it or display it everywhere in the kitchen without worrying it take up a lot of spaces. The bulky shape machine is not easy to handle, and it also consume a lot of time to operate it. With the compact one machine, the owner of the product will use it with ease. The second value that being offered through the product is it uses the high-quality plastic that are resistant to the high heat and scratches. Generally, a product that is made up of plastic encounter the same problem which is the low endurance of the product to the heat and its surface will leave with a lot of scratches after frequent usage. By using the high-quality of material will increase the satisfaction of users as it will benefit them. The third value that being offered is how the product will benefit the user in term of its functionality. The roll tray that are being used as the place where the raw foods are being placed on can be used as a food container. After the foods being dehydrated, the food will be left to cool down and then the user just uses the roll tray as the storage container. The dual functions that the roll tray provide will help the user to utilize it very easily.